DISEÑO ELÉCTRICO DE LA RED DE MEDIA Y BAJA TENSIÓN PARA EL PARQUE TEMÁTICO DE LA FACULTAD DE LA ENERGÍA, LAS INDUSTRIAS Y LOS RECURSOS NATURALES NO RENOVABLES-FEIRNNR” - Carlos Andres, Rivera Ruilova (2025)
This study consists of the design of the Medium and Low Voltage network for the Theme Park of the Faculty of Energy, Industries and Non-Renewable Natural Resources (FEIRNNR). First, the electrical infrastructure of the study site is raising with field visits and information gathering through the website of the Regional Electric Company of the South S.A (EERSSA), then the architectural plan of the theme park that is the case study is requested, this information was provided by the planning department of the National University of Loja (UNL), with this information the first objective is met, which consists of the raising of the existing electrical network. Now with the information of the existing network and with the information collected by the planning department, the design of the medium and low voltage network for the theme park is carried out, for the elaboration of the design the guidelines of the Property Units (UP) and the Construction Units (UC) of the Ministry of Energy and Non-Renewable Natural Resources (MERNNR) and the internal regulations of the EERSSA are followed. From the projected network design, the following information is obtained. The design includes the replacement of the 11-meter pole number 141852 with a 12-meter, 500 kg pole on Eduardo Kigman Avenue for the extension of the medium voltage network, a 10 kVA singlephase pad-mounted transformer, the installation of 24 meters of medium voltage conductor, 1,729 km of low voltage conductor, the construction of 46 underground wells, the excavation of 851,4 meters of trenches, the installation of 40 metal poles of 6 meters, and the installation of 24 W LED-type luminaires. Finally, the electrical design is prepared and will be presented to EERSSA for approval.